Multidimensional evaluation of mutual funds using performance ratios: a critical examination of technology sector mutual funds in India (Vallis Aurea, 2019)
Over the years, a number of performance indicators have been developed and used to assess the performance of mutual funds. The choice of these performance measures completely rests on the perception of the investor as to which measure conveys the information sought after by the investor and which information the investor considers would be meaningful in deciding the fate of his investments. Objective & Methodology: To evaluate the risk and return of selected technology sector mutual funds and to analyse the composite information conveyed by Sharpe’s ratio, Treynor’s ratio, upside and downside capture ratios.Results & Discussion: When the funds were analysed using Sharpe ratio, Treynor’s ratio upside capture ratio and downside capture ratio, the funds that performed the best in consideration to a particular measure may not be termed best when analysed with another performance gauges stressing on the fact that all the ratios should be analysed with an integrated perspective to derive any underlying information on the performance of the fund and that the choice of the benchmark which stands as a basis to assess performance of the fund is crucial.